The Earth is blue as an orange [videorecording (DVD)] - Tsvietkov, Viacheslav (Cinematographer) (Film Movement, 2022)
Krasnohorivka: a town on the front lines of the war-torn region of Eastern Ukraine. When poet/filmmaker Iryna Tsilyk first visits the Trofymchuk-Gladky family home, she is surprised by what she finds: while the outside world is made up of bombings and chaos, single parent Anna and her four children are managing to keep their home as a safe haven, full of life and full of light. Every member of the family has a passion for cinema, so it feels natural for them to shoot a film inspired by their own life during a time of war. The creative process raises the question of what kind of impact cinema might have during times of disaster, and how to picture war through the camera's lens. For Anna and the children, transforming trauma into a work of art is the ultimate way to stay human.